Use of Logbook Data to Assess 34-Hour Restart Charges. Issue 1 (January 2014) - Short, Jeffrey
The Federal Motor Carrier Safety Administration's (FMCSA) hours-of-service (HOS) rules govern the number of hours that a commercial driver may be on duty and operate a commercial motor vehicle and how much rest is required between periods of work. Recent changes to the HOS, which included a change to the 34-h restart rule, were supported by an FMCSA regulatory impact analysis (RIA) that assessed the costs and benefits of the changes. The foundation of this analysis was logbook data from a small sample of carriers undergoing FMCSA safety audits and compliance reviews and thus more likely to have compliance issues. To assess the accuracy of the FMCSA cost–benefit analysis, which found a net benefit of $133 million annually for the new restart provisions, the American Transportation Research Institute (ATRI) research team replicated the most critical analyses of the RIA. As part of this process, a larger logbook data set that represented normal trucking operations was utilized. ATRI found that FMCSA's intense-schedule drivers, a group that was critical to FMCSA's net benefit findings, did not exist within normal carrier operations. Consequently, the agency's cost–benefit results were found to be overestimated. Analysis of the normal logbook data showed that a net loss, not a net benefit, would result from the new restart provisions. In addition, costs not captured by FMCSA's analysis were incorporated in the analysis to show an annual loss of $189 million considering that the average driver might lose a modest 15 min of productivity per week because of the new provisions.